Productivity of noun paradigms: the morphological integrations of loanwords and the variation of inflectional paradigms - Kamandulytė-Merfeldienė, Laura (Lietuvių kalba, 2010)
The paper introduces the results of the synchronic analysis of the productivity of noun paradigms. On the basis of the theory of Natural Morphology, to identify productive paradigms, two criteria have been selected: a) the variation of inflectional paradigms and b) the morphological integration of new loanwords. The variation of inflectional paradigms is treated as confusing inflections of different paradigms. The new morphologically integrated loanwords refer to words of foreign origin of the last decade which have been used with Lithuanian inflections. Both criteria of paradigm productivity have been analysed on the basis of the Corpus of Spoken Lithuanian compiled in 2006-2008 (http://donelaitis.vdu.lt/~andrius/SKT5/5SKT-paiesk.php); it provides an opportunity to investigate samples of natural spontaneous language. The analysis of the morphological integration of loanwords has proved the initial hypothesis that new loanwords adopt natural inflections, i.e. inflections of productive paradigms. The investigation of the variation of inflectional paradigms has shown that the words undergo paradigm changes from unproductive to productive inflectional paradigms. The investigation has revealed that masculine paradigms are more productive in contemporary Lithuanian than feminine paradigms. The inflections of masculine paradigms are usually attached to new loanwords and replace the inflections of less productive paradigms. The 1st male paradigm (-as) seems to be the most productive. The 3rd male paradigm (-is, -ys) has turned out to be less productive. Rather stable but unproductive is the 6th female paradigm (-a); it has few loanwords; the nouns of this paradigm are not used with the inflections of other paradigms. Other paradigms of the noun could be treated either as stable (8th paradigm (-ė)) or unproductive (4th (-us), 11th (-, -iui) and 12th (-, -iai); 9th (-is, -iai) and 10th (-is, -iui) paradigms).
Keywords: none